Meningkatkan Strategi Belajar Peserta Didik Melalui Layanan Bimbingan Kelompok Menggunakan Metode Cooperatif Learning - Saputri, Sandra Sari; Maftuhah, Siti; Masril, Masril (JKI (Jurnal Konseling Indonesia), 2023)
Weak student learning strategies lead to low learning outcomes so group guidance is carried out using the discussion method, but the activity objectives have not been achieved. Therefore used a group guidance approach with cooperative learning methods to improve student learning strategies. The research subjects were students of class VII UPT SMPN 2 Sitiung. This study uses the Guidance and Counseling Action Research method. Data was tested using the Paired Samples Test (T test). The results of the group guidance approach with the Cooperative Learning method can significantly improve student learning strategies.